MENINGKATKAN KEMAMPUAN SPASIAL SISWA DENGAN PEMBELAJARAN MELALUI MEDIA VISUAL - Rohmah Pila Khoriyani; Martin Suhendra (EDUCATIONAL JOURNAL : General and Specific Research, 2022)
This paper aim of overcoming the weakness of students' mathematical spatial abilities in geometry. By using visual learning media, it is hoped that it can improve students' spatial abilities. As for conducting a literature review to examine how visual learning media in the form of geogebra, cabri 3D, or learning videos can improve students' spatial abilities, which are closely related to their abilities in geometry, The results of the research studies conducted are then described to present the results of implementing learning with visual media, which have an impact on increasing students' spatial abilities. By increasing students' spatial abilities, it is expected that students can fully understand geometry material. In addition, increasing students' spatial abilities is expected to foster students' motivation in learning mathematics.